Constitutionalism and rights protection in Mexico and Brazil: comparative remarks - Giménez, Francisca Pou (Revista de Investigações Constitucionais, 2018)
Comparative exercises between constitutional law in Brazil and in Mexico may seem destined to be exercises of identifying a reduced set of commonalities in an ocean of difference. The article, however, aims to suggest to what extent the opposite might be closer to the truth, and provide some sense of the amount of parallels between the two countries when viewed through constitutional lenses. Despite divergent paths of historical evolution in the XIX and the XX centuries, there are elements that confer to contemporary constitutional systems in Brazil and Mexico an air of commonality. The article underlines at least three of them: (i) commonalities in patterns of constitutional genesis and change; (ii) the existence of generous constitutional declarations of rights coupled with a varied assortment of rights-protecting channels in both places; and (iii) the existence in the two countries of old Supreme Courts with extensive jurisdictional menus and ample space for transformative action at their disposal. On the other hand, the main differences identified and analyzed in the article occur in the domain of rights protection and include the system of judicial enforcement of rights and the public profile of the two Supreme Courts.